The Efficiency and Equity Consequences of Two-Part Tariffs in Electricity Pricing - Naughton, Michael C. (The Review of Economics and Statistics, 1986)
Ahstrat t-This paper evaluates electricity two-part tariffs with both efficiency and equity criteria. The efficiency of tariffs is analyzed by studying the relation between price and marginal cost for both customer connection and variable output. The equity of tariffs is addressed by an analysis of cross subsidization. To address these issues, this paper presents a multiproduct cost function that can provide information on output and connection marginal costs for each customer class. Using a 1980 cross section of electric utilities, it is shown that prices are not set in a first-best efficient manner, and least favor the commercial class.